Itinerários terapêuticos de surdos em busca de cuidados em saúde mental - Francke, Ingrid D'Avila (Universidade do Vale do Rio dos Sinos, 2018)
This thesis is the result of an ethnographic experience with three women and one man, all Deaf and Libras users, which enabled a seven-month follow-up in the research field. Several reports were seized, through interviews and participant observations, of their relations with a predominantly listening society. The main objective was to explore the perspective of Deaf people on mental health, their life trajectories and their search for health care. The first article aimed to discuss how stigma and notions of disability are articulated in family relationships and institutions in a social process that restricts the autonomy and citizenship of Deaf people based on a case study. Based on Sofia's narratives about her experiences with family, education and work, it is discussed how much the recognition of her identity as a Deaf woman involved a continuous and complex search for social belonging, challenged by the stigma of disability and threats to her mental health . Alternative paths for seeking citizenship were woven and supported by the possibility of participation and social belonging with Deaf groups and communities. The social challenge of broadening the understanding of citizenship from the perspective of diversity and respect was discussed, reflecting on scenarios in which the identity and dignity of the Deaf are constructed and reconstructed. The second article aimed to understand the health care trajectories of Deaf people, describing experiences and meanings associated with health problems and their support network. Narratives of four participants about their relationship with mental health care were analyzed. The data showed that the meaning of “mental health” is seen as synonymous with yet another deficiency or maladjustment often attributed to the deaf, generating very marked experiences of stigmatization, some already experienced in childhood. Experiences of lack of autonomy for health care, unpreparedness and distancing from the formal care networks regarding the Deaf culture and a generalized social listening center resulted in avoidance strategies, moving the Deaf away from care alternatives, particularly in mental health. On the other hand, Deaf communities proved to be an important resource among the Deaf, indicating that expanding the dialogue with health policies could be a way to expand their social participation and reduce inequities in access to care.
Keywords: Surdez; Itinerário terapêutico; Saúde mental; Estigma; Atenção à saúde; Deafness; Therapeutic itinerary; Mental health; Stigma; Health care; ACCNPQ::Ciências da Saúde::Saúde Coletiva